Si, Mn함유 IF 고강도강의 소둔거동 및 도금특성에 미치는 이슬점 온도의 영향 - 전선호; Sun Ho Jeon; 신광수; Kwang Soo Shin; 손호상; Ho Sang Sohn; 김대룡; Dai Ryong Kim (대한금속·재료학회지, 46(7), 2008)
The effect of dewpoints on annealing behavior and coating characteristics such as wettability and galvannealing kinetics was studied by annealing 0.3wt%Si-0.1~0.4wt% Mn added interstitial-free high strength steels(IF-HSS). The 0.3wt%Si-0.1wt%Mn steel exhibited good wettability with molten zinc and galvannealing kinetics after annealing when the dewpoint of H2-N2 mixed gas was above -20℃. It is shown that the wettability and galvannealing kinetics are directly related to the coverage of the external(surface) oxide formed by selective oxidation during annealing. At N2-15%H2 annealing atmosphere, the increase of dewpoint results in a gradual transition from external to internal selective oxidation. The decrease of external oxidation of alloying elements with a concurrent increase of their subsurface enrichment in the substrate, showing a larger surface area that was free of oxide particles, contributed to the improved wettability and galvannealing kinetics. On the other hand, the corresponding wettability and galvannealing kinetics were deteriorated with the dewpoints below -20℃. The continuous oxide layer of network and/or film type was formed on the steel surface, leading to the poor wettability and galvannealing kinetics. It causes a high contact angle between annealed surface and molten zinc and plays an interrupting role in interdiffusion of Zn and Fe during galvannealing process.